The Impact of the Implementation of Accrual Accounting and Corruption Control on the SDGs Globally - Patricia Talbolt P Totuuk; Andi Chairil Furqan; Muliati Muliati; Phatra Anggana Djuri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The impact of accrual-based accounting and corruption prevention on the global accomplishment of the Sustainable Development Goals (SDGs) is examined in this study. Using secondary data from 151 nations spanning the years 2020–2024, a quantitative research approach produced a total of 755 observations. The World Bank, the Sustainable Development Report, Transparency International, and the International Federation of Accountants (IFAC) were among the international databases from which the data were gathered. Purposive sampling was used to choose the research sample based on information about the implementation of accrual accounting, the Corruption Perceptions Index (CPI), SDG scores, and GDP per capita. The Random Effect Model (REM) was used for panel data regression analysis, with LNGDP included as a control variable and institutional and stakeholder theories acting as the theoretical underpinnings. The results show that accrual-based accounting has a positive and significant impact on achieving the SDGs globally. This result indicates that greater transparency and accountability in public financial reporting contribute to better resource management and more effective development decision-making. In addition, corruption control is found to positively affect SDG achievement, suggesting that sound governance enhances budget efficiency and supports the implementation of sustainable development programs. Additionally, the control variable, LNGDP, shows a positive effect, suggesting that a nation's economic potential contributes to better SDG accomplishment. Overall, this study emphasises that the implementation of accrual-based accounting, more robust anti-corruption policies, and improved institutional quality are crucial components in advancing the realisation of sustainable development globally.